24-hour Fire Produced Effect on Reinforced Recycled Aggregates Concrete Beams - Buller, A. H.; Oad, M.; Memon, B. A.; Sohu, S. (Engineering, Technology & Applied Science Research, 2019)
In this article, the effect of prolonged fire (24-hour duration) on reinforced concrete beams made with recycled aggregates from demolished concrete was experimentally investigated. Demolished concrete was used recycled coarse aggregates in equal proportion with natural coarse aggregates. Normal and rich mix concrete with water-cement ratio equal to 0.54 were used. As a control specimen, beams with all-natural aggregates were also cast to compare with the results of the proposed beams. All beams were cured for 28 days and exposed to fire at 1000°C in an oven for 24 hours. After the elapse of this fire period, the beams were allowed to air cool, followed by testing till failure in a universal load testing machine. Comparison of the test results shows that rich mix concrete beams more reduction in flexural strength, more increase in maximum load carrying capacity and deflection than normal mix beams. The maximum reduction in flexural strength was 32.41% for beams cast with 50% RCA and rich mix. Although the fire duration used in this study is rare, yet the outcome provides guidelines for taking proper decisions for retrofitting/strengthening of the fire affected structure before putting it back in service.